112k views
4 votes
Simplify completely quantity of x squared minus 15 x plus 36 all over 5 x minus 60.

User Andell
by
5.7k points

2 Answers

6 votes
I assume you mean (x^2 - 15*x - 36) / (5x - 60). Notice that you can factor a 5 out of the denumerator (the bottom), to get 5 * (x - 12). You could then try factoring the numerator (the top part), and you will probably be able to cancel out a term on top and bottom.
User Christian Ziebarth
by
6.0k points
6 votes

Answer: The simplified value of the given expression will be
(x-3)/(5)

Explanation:

The expression of the given statement becomes:


(x^2-15x+36)/(5x-60)

To solve the above expression, we need to factorize the quadratic equation by middle term splitting:


\Rightarrow (x^2-15x+36)/(5x-60)=(x^2-12x-3x+36)/(5(x-12))\\\\\Rightarrow (x^2-12x-3x+36)/(5(x-12))=(x(x-12)-3(x-12))/(5(x-12))\\\\\Rightarrow (x(x-12)-3(x-12))/(5(x-12))=((x-3)(x-12))/(5(x-12))

Omitting out the factor '(x - 12)' from denominator and numerator, we get:


\Rightarrow ((x-3)(x-12))/(5(x-12))=(x-3)/(5)

Hence, the simplified value of the given expression will be
(x-3)/(5)

User Techy
by
5.1k points